2015
DOI: 10.4172/2378-5756.1000350
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Emotional Disturbance in Children with Hearing Impairment and Intellectual Disability

Abstract: Present study aims to investigate the prevalence of emotional disturbance among children with hearing impairment and intellectually disabled. Sample of 67 children was collected from different rehabilitation centers of Karachi, Pakistan. Intellectually disabled were 35 and with hearing impairment were 32 children. Sample age range was 12 to 18 years with mean age of 14.98 years. One to one session was conducted with parents in order to get history of presenting problem of the child. After getting demographic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Comparisons have been made of the link between mental health and hearing loss and with other types of impairment. In a study conducted in Pakistan, 32 children (12–18 years) with hearing loss from rehabilitation centres were found to have a significantly higher risk of psychological conditions than the control group of children with intellectual disabilities [56]. In contrast, an Indian study by Singh et al (1988) found a similar proportion (15%) of 275 children (4–16 years) in each of three groups (hearing loss, visual impairment and controls) had classifiable mental health conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons have been made of the link between mental health and hearing loss and with other types of impairment. In a study conducted in Pakistan, 32 children (12–18 years) with hearing loss from rehabilitation centres were found to have a significantly higher risk of psychological conditions than the control group of children with intellectual disabilities [56]. In contrast, an Indian study by Singh et al (1988) found a similar proportion (15%) of 275 children (4–16 years) in each of three groups (hearing loss, visual impairment and controls) had classifiable mental health conditions (i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Ten of these 12 studies provided evidence that the prevalence of mental disorders is higher in people with hearing loss than in comparison groups without hearing loss. Furthermore, Abbas and Reddy found that hearing loss was also associated with higher incidence of mental health conditions than conditions associated with other impairments [56]. Nehra et al (1997) found the severity of hearing loss was related to the improvement in mental function after intervention (hearing aids) [50].…”
Section: Discussionmentioning
confidence: 99%